Effects of Exercise on Patients Important Outcomes in Older People With Sarcopenia: An Umbrella Review of Meta-Analyses of Randomized Controlled Trials - Shen, Yanjiao; Liu, Dan; Li, Sheyu; He, Yazhou; Tan, Fucha; Sun, Xuelian; Li, Daiping; Xia, Xin; Hao, Qiukui (Frontiers in Medicine, 2022)
Background Many clinical practice guidelines strongly recommend exercise as an intervention for patients with sarcopenia. However, the significance of exercise on patient-important outcomes in older adults with sarcopenia is inconsistent when considering available minimal important differences. To synthesize current systematic review and meta-analyses evidence on the efficacy of exercise on patient-important outcomes in the treatment of sarcopenia in older adults. Methods We searched MEDLINE, EMBASE, Cochrane Library (Cochrane database of systematic review, CDSR) via OvidSP and Web of science until April 2021 and reference lists. Two independent investigators performed abstracted and title screening, assessed the full text and quality of evidence. This umbrella review included systematic reviews and meta-analyses of randomized controlled trials (RCTs). Eligible reviews aim to evaluate the effect of exercise on patient-important sarcopenic outcomes (muscle or physical function, mortality, and quality of life) in treating sarcopenia in older people. We used the minimally important differences (MIDs) of these outcomes to assess if the effects of exercise matter to patients. Results This umbrella review provided a broad overview of the existing evidence and evaluated the systematic reviews' methodological quality and evidence for all these associations. In older patients with sarcopenia, moderate- to high-quality evidence showed that exercise intervention probably increases walking speed and improved physical performance (measured by TUG test); exercise may increase the muscle strength (grip strength, keen extension strength); but the effect size for grip strength probably too small to achieve patients important changes. Evidence for older people with sarcopenic obesity is limited, and we found the consistent effect of exercise interventions on grip strength and usual walking speed. Conclusion Exercise has a positive and important effect on physical performance for older adults with sarcopenia, which supports leaving the current recommendations unchanged. New systematic reviews to summarize the effect of exercise on the quality of life are warranted to fill the current evidence gap.